Analysis of Managerial Perception of Financial Statement Transparency: A Qualitative Study at Company XYZ - Alfina Sulistiani; Mutiara Fadhlina; Lia Uzliawati (International Forum of Researchers and Lecturers, 2025)
This study explores managerial perceptions of financial statement transparency at Company XYZ and identifies the challenges and benefits associated with its implementation. Transparency in financial reporting is critical for enhancing accountability and stakeholder trust. Using a qualitative approach, in-depth interviews were conducted with managers from various departments to understand their views on transparency. The findings reveal that while managers recognize the importance of transparency in fostering stakeholder confidence and reducing risks related to financial ambiguity, they face significant challenges such as limited resources, complex regulatory requirements, and communication barriers with external stakeholders. Despite these obstacles, managers acknowledge that transparency offers substantial benefits, including improved corporate reputation, increased investor trust, and enhanced operational efficiency. This study contributes to the literature by providing insights into the practical barriers and strategic advantages of transparency, offering recommendations for companies aiming to improve their financial reporting practices.